Enhancement of visual attention precedes the emergence of novel metaphor interpretations - Terai, Asuka; Nakagawa, Masanori; Kusumi, Takashi; Koike, Yasuharu; Jimura, Koji (Frontiers in Psychology, 2015)
Emergence of creative ideas often involves sudden linking of unrelated ideas. Here we demonstrate that the production of insights about novel metaphor was preceded by prolonged visual inspection of metaphorical sentences. The participants made free spoken responses in a task requiring the generation of semantic interpretations about visually-presented sentences, where gaze locations were continuously monitored. We found that creative interpretations were primarily generated from novel metaphorical expressions, rather than from conventional expressions. Moreover, presented words within novel metaphors were visually inspected for longer periods specifically before creative interpretations were produced. Interestingly, prolonged gazes occurred several seconds ( 8 sec) prior to the generation of creative interpretations, particularly, in the case of the topic word within the metaphor. These results demonstrate latent cognitive process meditating the emergence of insights, and suggest that the prior visual inspection prompted the semantic representation of the metaphorical sentences, which eventually facilitates creative ideas.